1998
DOI: 10.2307/1592484
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Seven Chinese Isolates of Infectious Bursal Disease Virus: Classical, Very Virulent, and Variant Strains

Abstract: Seven infectious bursal disease virus (IBDV) strains isolated from China have been characterized in this study, including a classical strain CJ801, an attenuated strain GZ911, a variant strain GZ902, and four very virulent strains G9201, G9302, F9502, and HK46. With the use of reverse transcription-polymerase chain reaction, the full-length VP2 genes were amplified and the hypervariable regions were sequenced. Protein sequences of the hypervariable region (a.a. 143-382) of the field isolates confirmed their id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 28 publications
3
64
0
1
Order By: Relevance
“…This study revealed that vvIBDVs displayed divergence up to 10.6% from vaccinalstrains. The amino acids at P222A, V256I, L294I and N299S are conserved in vvIBDVs of Indian and Pakistani isolates [2,41]. The same findings were observed in Senegalese vvIBDVs belonging to African linages.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This study revealed that vvIBDVs displayed divergence up to 10.6% from vaccinalstrains. The amino acids at P222A, V256I, L294I and N299S are conserved in vvIBDVs of Indian and Pakistani isolates [2,41]. The same findings were observed in Senegalese vvIBDVs belonging to African linages.…”
Section: Discussionsupporting
confidence: 72%
“…Selected sequences were aligned by Neighbour-Joining (NJ) Method. This information provides many important aspects [2,9,10]. Topologically, the phylogenetic tree revealed that IBDVs separated into three main groups, namely vvIBD viruses, classic/variant viruses and attenuated/vaccine strains.…”
Section: Phylogenetic Analysis Of Vp2-hvrmentioning
confidence: 99%
See 3 more Smart Citations